(untitled) (Scientific journal of the Fergana State University, 2023)
The state of development of modern technologies depends primarily on the intellectual potential of society, that is, on the development of the education sector. Issues of the content and quality of education are considered as a priority. In developed and developing countries of the world, special attention is paid to informatization of education. Ways of developing education and increasing its effectiveness are considered, special attention is paid to the introduction of new information technologies in education.